Transformasi Strategi Marketing Syariah dalam Pengembangan Bisnis Perbankan Syariah Modern - Nursaman, Nursaman; Syam, Surya Darma (JIOSE: Journal of Indonesian Sharia Economics, 2025)
The background of this research stems from the need of Islamic banking to develop marketing strategies that are not only profit-oriented but also consistently uphold compliance with Sharia principles. This study employs a library research method with a qualitative approach, while data were collected through digital documentation from various related literatures. The findings indicate that Sharia marketing management in banking requires concrete analyses and steps, including goal setting, identification of characteristics, determination of concepts and foundations, understanding of the environment, strategy formulation, market segmentation, pricing strategies, promotional strategies, and efforts to enhance customer satisfaction in accordance with Sharia principles. The transformation of Sharia marketing strategies in Islamic banking in the modern era demands synergy between human resource competencies, accurate market segmentation, product innovation, and the utilization of digital technology based on Sharia principles. These strategies are not only oriented toward increasing profitability but also emphasize public benefit, sustainability, and social justice as the embodiment of maqāṣid al-sharīʿah. The findings affirm the importance of integrating Sharia values and digitalization into marketing management practices to strengthen the competitiveness and sustainability of Islamic banking in the modern era.